From Gallica to Gallica 2 and More: A Survey of the Digitisation Projects at the BnF - Sara Yontan Musnik (Türk Kütüphaneciliği)
This paper will attempt to present a survey of the digitisation project(s) at the French national library in Paris. It will mention the various stages of this venture from its very beginnings until today, highlighting the achievements, but also pointing at the difficulties encountered, both material and theoretical. The talk will close with the question of what digitised collection building may mean for an encyclopaedic and comprehensive heritage library.